1998
DOI: 10.1046/j.1365-2249.1998.00610.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity to tropomyosin isoforms in ulcerative colitis (UC) patients and unaffected relatives

Abstract: Autoimmunity to cytoskeletal protein tropomyosin (TM) has been demonstrated in UC. However, the TM isoforms involved in this IgG-mediated autoimmune response in UC and the possible presence of serum IgG antibodies against TM (hTMs IgG) in unaffected UC relatives are unknown. The aim of this study was to investigate the human TM (hTM) isoforms recognized by serum IgG from UC and to explore whether hTM IgG antibodies are present in healthy UC relatives. We studied 33 UC patients with 58 unaffected relatives, 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…21 Antibodies to human tropomyosin isoform 5 were found in 19% of CD patients, in 64% of UC patients, and in 4% of healthy controls. 22 Antibodies to complement C3 were found in 23% of IBD patients, but not in healthy controls. 23 Antibodies to pancreatic tissue were found in 39% of CD patients, 4% of UC patients, but not in healthy controls or patients with celiac disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…21 Antibodies to human tropomyosin isoform 5 were found in 19% of CD patients, in 64% of UC patients, and in 4% of healthy controls. 22 Antibodies to complement C3 were found in 23% of IBD patients, but not in healthy controls. 23 Antibodies to pancreatic tissue were found in 39% of CD patients, 4% of UC patients, but not in healthy controls or patients with celiac disease.…”
Section: Discussionmentioning
confidence: 98%
“…Antibodies to these antigens have been described in CD, UC, and IBD, respectively. [21][22][23] To our knowledge, antibodies to FAM84A have not been described previously. FAM84A is a gene whose expression has been reported to be upregulated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the cell membrane hTM5 is found complexed with a 200 kDa colonic epithelial protein (CEP), and this complex is speculated to serve as the true target for the Das-1 antibody [27] . Antibodies against hTM5 have been detected in UC patients without PSC [28] , and antihTM5 in UC sera has recently been shown to induce cytotoxicity against colonic epithelial cells in vitro [29] . In PSC patients without concomitant UC, a single study identified antibodies against a 9-amino acid sequence from hTM (not isoform specific) in 100% (8/8) of patients as compared with 69% (33/48) of UC patients and 0/6 PBC patients [30] .…”
Section: Antibodies Against Biliary and Colonic Epithelial Antigensmentioning
confidence: 99%
“…Autoimmune mechanisms may play an important role in the pathogenesis of this disease. Various kinds of autoantibodies, such as anti-neutrophil cytoplasmic antibodies [1][2][3][4] and antitropomyosin antibodies, [5][6][7] have been demonstrated in serum samples of patients with ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%